Tanshinone I promotes angiogenesis and improves ventricular remodeling post-myocardial infarction via ALDH2 signaling-mediated ferroptosis inhibition - Zhang, Feng; Li, Lei; Liu, Qian; Wang, Wen-Long; Wang, Zhi-Xin; Song, Rong-Qiang; Sun, Jian; Zhang, Yi-Yi; Ren, Xin-Chen; Wang, Dong; Wu, Yu-Ting (Frontiers in Pharmacology, 2025)
BackgroundTanshinone I (Tan I) has diverse cardioprotective effects, including improving post-myocardial infarction (MI) ventricular remodeling. Ventricular remodeling can be improved by inhibiting endothelial cell (EC) ferroptosis to promote post-MI angiogenesis, but how Tan I does this remains unclear. Thus, we investigated how EC ferroptosis mediates post-MI angiogenesis and Tan I's role in this process.MethodsIn vivo experiments: A mouse model of MI was established to evaluate cardiac function, myocardial injury, collagen deposition, and EC ferroptosis. CD31 expression was measured to assess angiogenesis, and western blot analysis was used to detect ALDH2 signaling-related proteins (ALDH2, xCT, GPX4). In vitro experiments: Ferroptotic human umbilical vein endothelial cells (HUVECs) induced by erastin were treated with Tan I to assess ferroptosis, cell proliferation, migration, and tubular network formation. Western blot analysis was used to detect ALDH2 signaling-related proteins. Additionally, the role of Tan I was further verified by using the ferroptosis inhibitor ferrostatin-1, the ALDH2 agonist Alda-1, or the ALDH2 inhibitor daidzein in vitro and in vivo models, respectively.ResultsWe found that Tan I improved post-infarction cardiac function and myocardial injury, inhibited post-infarction collagen deposition and EC ferroptosis, and promoted CD31 expression in vivo by activating ALDH2 and promoting ALDH2 signaling-related protein levels. Additionally, Tan I inhibited ferroptosis, promoted proliferation and migration, and enhanced tubular network formation in HUVECs in vitro by activating ALDH2 and promoting ALDH2 signaling-related protein levels.ConclusionTan I may improve ventricular remodeling by activating ALDH2 signaling, inhibiting EC ferroptosis, and promoting angiogenesis.